Manajemen Resiko Kredit pada Perbankan Syariah - Eristiana Choirun Nisa; Nuvailah Rosiyah; Rosa Try Octavia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the implementation of credit risk management in Islamic banking, which is a crucial aspect in maintaining business stability and sustainability. The research focuses on identifying credit risk control strategies, such as supervisory oversight by the board of commissioners, risk management policies, and internal control systems. The research method used is a literature review, examining various sources, including journals, books, and official documents. The article shows that credit risks in Islamic banking arise from customers' failure to meet payment obligations and involve concentration and counterparty risks. Islamic banks apply several strategies to address non-performing loans, such as rescheduling, restructuring, reconditioning, and, when necessary, collateral seizure. The implementation of credit risk management helps banks reduce potential losses and improve operational efficiency. Effective credit risk management enables Islamic banks to mitigate losses and maintain customer trust while adhering to Sharia principles and OJK regulations. With the right strategies, Islamic banks can ensure financial stability and sustain long-term growth..